A qualitative exploration of the feasibility and acceptability of Meaning-Centered Psychotherapy for Cancer Caregivers. Issue 5 (October 2022) - Applebaum, A. J.; Roberts, K. E.; Lynch, K.; Gebert, R.; Loschiavo, M.; Behrens, M.; Walsh, L. E.; Polacek, L. C.; Diamond, E. L.; Breitbart, W. S.
Abstract: Objective: Caregivers of patients with cancer are at significant risk for existential distress. Such distress negatively impacts caregivers' quality of life and capacity to serve in their role as healthcare proxies, and ultimately, contributes to poor bereavement outcomes. Our team developed Meaning-Centered Psychotherapy for Cancer Caregivers (MCP-C), the first targeted psychosocial intervention that directly addresses existential distress in caregivers. Method: Nine caregivers of patients with glioblastoma multiforme (GBM) enrolled in a pilot randomized controlled trial evaluating the feasibility, acceptability, and effects of MCP-C, and completed in-depth interviews about their experience in the therapy. One focus group with three MCP-C interventionists was also completed. Results: Four key themes emerged from interviews: (1) MCP-C validated caregivers' experience of caregiving; (2) MCP-C helped participants reframe their "caregiving identity" as a facet of their larger self-identity, by placing caregiving in the context of their life's journey; (3) MCP-C enabled caregivers to find ways to assert their agency through caregiving; and (4) the structure and sequence of sessions made MCP-C accessible and feasible. Feedback from interventionists highlighted several potential manual changes and overall ways in which MCP-C can help facilitate caregivers' openness to discussing death and engaging in advanced care planning discussions with the patient. Significance of results: The overarching goal of MCP-C is to allow caregivers to concurrently experience meaning and suffering; the intervention does not seek to deny the reality of challenges endured by caregivers, but instead to foster a connection to meaning and purpose alongside their suffering. Through in-depth interviews with caregivers and a focus group with MCP interventionists, we have refined and improved our MCP-C manual so that it can most effectively assist caregivers in experiencing meaning and purpose, despite inevitable suffering.